Model Pengembangan Pelet Biomassa dari Sampah Daun dan Ranting untuk Mendukung Transisi Energi dan Pengelolaan Sampah Berkelanjutan di Cilacap - Wardani, Nur Indah; Hestyani, Dewi; Prastya, Andika; Prabowo, Dian; Restian, Ahmad; Nugroho, Adi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia faces dual challenges in the form of high dependence on coal and increased volumes of leaf and ranting organic waste. This study studied the development of biomass pellets from leaf litter and ranting as renewable energy (EBT) initiated by PT Building Solutions Indonesia (SBI) Cilacap together with Cilacap State Polytechnic. Analysis includes technical concepts, environmental impacts through a life cycle approach, as well as implementation potentials and challenges. Results show the use of biomass pellets can decrease net greenhouse gas and methane gas emissions from leaf burning and ranting by the community, as well as supporting the circular economy model. The main challenges include production energy consumption and particulate emission control. The concept is technically and ecologically feasible with optimization and policy support as a prerequisite for commercialization.